2021
DOI: 10.1158/1538-7445.am2021-626
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 626: The neoantigen and immune landscape of epithelial mesenchymal transition (EMT) low and high score serous ovarian cancers

Abstract: Background: Apart from its role in ovarian cancer progression, epithelial-mesenchymal transition (EMT) can promote chemotherapy resistance. We aimed to analyze how the EMT score would affect the tumor microenvironment in ovarian cancer. Methods: cBioportal was queried to obtain The Cancer Genome Atlas (TCGA) data for the serous ovarian cancer (SOC) cohort (TCGA, 585 patients). The neoantigen prediction data was derived from the CloudNeo pipeline using TCGA mutation calling. EMT scores were calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lien et al (44) found a high TIL density in 34% of metaplastic breast carcinoma, a tumor similar to CS both in its association with epithelialmesenchymal transformation (EMT) and extremely low rate of MSI (44,45). A study of ovarian serous carcinoma has suggested that tumors with high EMT scores may have higher numbers of neo-antigens compared to tumors with low EMT scores (46). Whether EMT causes increase in immunogenicity of CS leading to influx of TILs needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Lien et al (44) found a high TIL density in 34% of metaplastic breast carcinoma, a tumor similar to CS both in its association with epithelialmesenchymal transformation (EMT) and extremely low rate of MSI (44,45). A study of ovarian serous carcinoma has suggested that tumors with high EMT scores may have higher numbers of neo-antigens compared to tumors with low EMT scores (46). Whether EMT causes increase in immunogenicity of CS leading to influx of TILs needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%